Characterisation of a travelling-wave parametric amplifier for improved qubit measurements - Nilsson, Hampus Renberg (My University, 2019)
In order to build a large-scale quantum computer, one of the requirements is high-fidelity multiplexed qubit readout, which in turn relies on the use of ultralow-noise amplifiers. While Josephson Parametric Amplifiers (JPAs), using a cavity with few Josephson junctions, have shown promising results for single qubit readout, they have limitations such as low saturation power and a gain-bandwidth product restriction. This makes them less suited for frequency multiplexed qubit readout. A current-pumped Josephson Travelling-Wave Parametric Amplifier (JTWPA), using 4-wave mixing in a lumped-element transmission line, features both high saturation power as well as no restriction on large bandwidth and high gain. This is possible due to multiple junctions and the lack of a cavity. However, also this current pumped JTWPA has an inherent problem, namely phase mismatch between the pump and the signal. This prevents exponential gain. In this thesis, a current pumped JTWPA using the resonant phase matching (RPM) technique to reduce the phase mismatch problem is studied and characterised. The JTWPA shows high gain, high saturation power and a large signal-to-noise ratio improvement. The JTWPA is also used for qubit readout, for which it clearly improves the readout fidelity.
Keywords: Nanovetenskap och nanoteknik; Nanoteknik; Nanoscience & Nanotechnology; Nano Technology